21st Century Japan–Philippines Strategic Partnership: Constraining China's Expansion in the South China Sea. Issue 2 (3rd April 2017) - De Castro, Renato Cruz
Abstract: The Philippines and Japan have evolved a security partnership in the face of China's maritime expansion in the South and East China Seas. The two countries pursue this security partnership through regular bilateral consultations among Philippine and Japanese heads of states, political leaders, defense ministry officials, and high-ranking military officers; joint naval exercises; and exploratory discussions for arms transfers and negotiations for a Status of Forces Agreement (SOFA) between Japan and the Philippines. Initially, Article 9 of Japan's 1947 Constitution hindered this security partnership. However, a recent reinterpretation of the pacifist constitution now allows Japan a collective self-defense "particularly to export arms to its allies and security partners and to deploy the JSDF overseas when necessary. Now, the challenge for Japan and the Philippines is to ensure the viability of their security partnership in the light of Philippine President Rodrigo Duterte's efforts to improve his country's relations with China.